PERSONNEL WORK PROCESS USING DIGITAL ECONOMY APPLICATION PROGRAMS - Albina Hashimova (Agora International Journal of Economical Sciences (AIJES), 2023)
Information technologies are emerging as systems that can meet the emerging demands of the business world in the conditions of increased competition and globalization. Today, with the help of information technology, it has become a value that can be multiplied and continuously produced and shared. Today, increased functionality with information technology has become the most important weapon of enterprises. Today, information technologies are used as the most important means of value creation, change, and renewal. The main purpose of the article is to determine the selection, training, and motivation of personnel for the digital economy. Also, the role of personnel emerging as a result of the digital revolution in the economy was particularly emphasized. The relevance of the study is that the increase in the labor productivity of the organization's employees and the increase in the efficiency of the personnel management system resulting from the use of digital technologies as a whole result in the increase of the competitiveness of the organizations.
Keywords: 330